International HR Management: Managing the Global Workforce with Knowledge Management - Pradana, Aldi Wahyu; Perkasa, Didin Hikmah (Lentera Ilmu Nusantara, 2024)
International human resource (HR) management has become an important focus for global companies in managing their workforce spread across different countries. In the face of unique cultural, linguistic, and regulatory challenges, companies need to develop effective strategies to ensure that employees around the world can operate in harmony and contribute to the organization's goals to the fullest. One approach that is increasingly emphasized in international HR management is the integration of Knowledge Management, which allows companies to collect, store, share, and use knowledge effectively across the organization. This study reviews the challenges in international human resource management, the role of Knowledge Management in supporting global human resource management, and the integration between the two. These integrations bring a number of benefits, including increased productivity, better decision-making, and greater employee engagement. With this holistic approach, companies can create an inclusive, collaborative, and innovative work environment in the midst of an increasingly complex and dynamic global market.